Timing and placement of cattle manure and/or gliricidia affects cotton and sunflower nutrient accumulation and biomass productivity - PRIMO, DÁRIO C.; MENEZES, RÔMULO S.C.; OLIVEIRA, FABIO F. DE; DUBEUX JÚNIOR, JOSÉ CARLOS B.; SAMPAIO, EVERARDO V.S.B. (Anais da Academia Brasileira de Ciências, 2018)
Organic fertilizers are a viable alternative to increase oilseed productivity in family agriculture systems. The study aimed to evaluate the effects of timing and placement of cattle manure and/or gliricidia (Gliricidia sepium Jacq. Walp) prunings on cotton (Gossipium hirsutum L.) and sunflower (Helianthus annuus L.) nutrient accumulation and biomass productivity. Experiments were carried out in 2010 and 2011 in Taperoá, Paraíba, Brazil. The organic fertilization treatments were: GI - gliricidia incorporated before planting; GS - gliricidia applied on surface 45 days after planting (DAP); MI + GI - manure and gliricidia incorporated before planting; MI + GS - manure incorporated before planting and gliricídia applied on the surface 45 DAP; MI - manure incorporated before planting; and T - with no organic fertilization. In 2010, treatment MI + GS increased N, P, and K accumulation in cotton (12 and 7 kg ha-1) as well as in sunflower (20 and 29 kg ha-1). In 2011, GI and GS treatments resulted in higher N, P, K accumulations in both crops. The highest cotton productivity in 2010 was obtained with MI + GS treatment (198 kg ha-1) and in 2011 with GS treatment (594 kg ha-1). For sunflower, MI + GS treatment yielded the highest productivity in 2010 (466 kg ha-1) and GI treatment in 2011 (3542 kg ha-1). GI and MI + GS treatments increased total biomass productivity for cotton and sunflower. The treatment that combined both cattle manure incorporated into the soil before planting and gliricidia applied on the surface 45 days after planting was the most viable management strategy.